Professional Zakat as an Instrument of Maqashid Syariah from the As-Syatibi Perspective in the Development of National Law in Indonesia - Ubbadul Adzkiya; Ahmad Rofiq; Muhlis; Ahmad Lukman Nugraha; Nur Izzati binti Ab Ghani (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to define professional zakat from the point of view of the concept of maqashid as-Shari'ah offered by Abu Ishaq Al-Syatibi. The author seeks to analyze the potential of zakat profession through the maqashid as-Shari'ah indicator. The research method used is qualitative with a normative approach. The results showed that zakat profession as a form of mashlahah in alleviating poverty. The author sees no nash inferring the prohibition of zakat profession (Lafadz al Amr wa al Anhy). At the time of the Prophet and Companions, the types of professions of the people at that time were limited to breeders, traders, miners and farmers (maqhasid at-tabi'ah). The study of zakat is also very dynamic (sukut al-Syar'i). Empowerment of the poor (Istiqra'). Zakat profession can realize benefits and be able to avoid chaos. The daruriyyat aspect, professional zakat is a support for the basic needs of the poor and poor, especially after the pandemic. The hajjyyat aspect, professional zakat is able to eliminate difficulties or make the maintenance of the five main elements even better. The aspect of tahsiniyyat, professional zakat is able to improve the standard of living of the poor community from recipients of zakat funds to zakat fund givers.